Nurul anak papa ku - Shahnon Ahmad, 1933- (Kuala Lumpur : Pustaka Jiwa Merdeka, 1999)
Fictionalized story of Dato' Seri Anwar Ibrahim's eldest daughter, Nurul Izzah.
"Sasterawan negara."
Koleksi Sumbangan : Dr. Syed Husin Ali.
Keywords: Malay fiction; Nurul Izzah Anwar, -- 1980- -- Fiction